A Review of Nutritional and Health Risk Factors for Low Birth Weight Infants in Indonesia - Nurwati, Yuni; Hardinsyah, Hardinsyah; Marliyati, Sri Anna; Santoso, Budi Iman; Angraini, Dewi (Jurnal Gizi dan Pangan, 2023)
This review aimed to identify the determinants of nutritional and health factors associated with high risk of Low Birth Weight (LBW) among infants in Indonesia. The review was conducted systematically based on all articles published between 2012–2022 in PubMed, ScienceDirect, and SAGE databases. In the end, four articles were used in this review. The results showed that potential risk factors associated with LBW are maternal nutritional factors such as Mid-Upper Arm Circumference (MUAC) (25%) and pre-pregnancy Body Mass Index (BMI) (50%), and maternal health factors that can be assessed during routine Antenatal Care (ANC). Therefore, identification of risk factors for LBW is important to minimize the incidence of LBW.